Comparative evaluation of MCP gene in worldwide strains of Megalocytivirus (Iridoviridae family) for early diagnostic marker. Issue 1 (15th September 2017) - Mishra, A; Nam, G‐H; Gim, J‐A; Lee, H‐E; Jo, A; Yoon, D; Oh, S; Kim, S; Kim, A; Kim, D‐H; Kim, Y C; Jeong, H D; et al.
Abstract: Members of the Iridoviridae family have been considered as aetiological agents of iridovirus diseases, causing fish mortalities and economic losses all over the world. Virus identification based on candidate gene sequencing is faster, more accurate and more reliable than other traditional phenotype methodologies. Iridoviridae viruses are covered by a protein shell (capsid) encoded by the important candidate gene, major capsid protein ( MCP ). In this study, we investigated the potential of the MCP gene for use in the diagnosis and identification of infections caused Megalocytivirus of the Iridoviridae family. We selected data of 66 Iridoviridae family isolates (53 strains of Megalocytivirus, eight strains of iridoviruses and five strains of Ranavirus ) infecting various species of fish distributed all over the world. A total of 53 strains of Megalocytivirus were used for designing the complete primer sets for identifying the most hypervariable region of the MCP gene. Further, our in silico analysis of 102 sequences of related and unrelated viruses reconfirms that primer sets could identify strains more specifically and offers a useful and fast alternative for routine clinical laboratory testing. Our findings suggest that phenotype observation along with diagnosis using universal primer sets can help detect infection or carriers at an early stage.